Bacteroides utilization for dietary polysaccharides and their beneficial effects on gut health - Jiaobo Cheng; Jielun Hu; Fang Geng; Shaoping Nie (Food Science and Human Wellness)
Polysaccharide was a class of macromolecular substance with various bioactive functions. Gut symbiotic microorganisms could utilize the polysaccharides from various sources, thus have important impact on human health. Bacteroides represented one of the dominant colonizers in the human gut. The utilization of polysaccharide by Bacteroides was important for supporting the function and stability of gut microbiota. After the degradation of polysaccharides by Bacteroides, gut microbes could ferment the monosaccharides and oligosaccharides degraded from polysaccharides into some metabolites, such as short-chain fatty acids (SCFAs), amino acids, etc. Among the metabolites, the SCFAs could have beneficial effects on gut health. This review summarized the niches of Bacteroides among gut microbiota, and also described the gene clusters and membrane proteins involved in the utilization processes of polysaccharide by gut Bacteroides. SCFAs could act as energy substrates for intestinal epithelial cells, inhibit histone deacetylases and activate G protein-coupled receptors. In addition, the future perspectives in investigating new degradation pathways for polysaccharide, and using polysaccharides or their metabolites as therapeutic approaches for diseases mediated by the gut dysbiosis were also provided.